Syria’s ordeal: A modern state’s disintegration in an age of fake news and superpower regional rivalry - William R. Stanley (Studia z Geografii Politycznej i Historycznej, 2019)
The negative impact of globalization is readily observed in today’s Syria. Ravished by seven years of internal conflict stimulated initially by Tunisia’s Arab awakening, this once proud state has become a magnet for religious fanatics and their wealthy sponsors in conservative Saudi Arabia and other countries far and near seeking geopolitical advantage. Not least Syria has experienced the seemingly futile endeavors by those in the United Nations and elsewhere seeking a solution to this country’s enduring turmoil. Military intervention by Iran and Russia has changed the configuration of the conflict at the critical point in time when Israeli and American intervention provides a dangerous environment for superpower conflict. All the while, Syrians remaining in the country suffer, and those seeking safety elsewhere are threatening to destabilize Lebanon, Turkey and Jordan and, farther afield, the cohesion of the European Community.